Analisis Perawatan dan Pemeliharaan Kendaraan PKP-PK Terhadap Operasi Pemadaman - Supri Supri; M.leon dirgantara; Cevin Oktorison (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Airport Rescue and Fire Fighting (ARFF) is a unit at the airport that is responsible for handling aviation and fire emergencies. This study discusses the maintenance and care of ARFF vehicles at the airport. Maintenance is interpreted as an activity carried out systematically to ensure that facilities function effectively and efficiently. Maintenance includes preventive and corrective actions to maintain the operational readiness of ARFF vehicles. The purpose of this study is to analyze the effect of vehicle maintenance and care on firefighting operations. This study also aims to determine the maintenance and care of vehicles that affect readiness in carrying out firefighting operations and their impacts. The method used in this study is a literature review (library research), which involves collecting and analyzing data from various relevant literature sources. This study focuses on previous studies on the maintenance and care of ARFF vehicles and their influence on the effectiveness of firefighting operations. The results of the study show that good maintenance and care have a positive effect on firefighting operations. Regular maintenance and systematic maintenance increase the reliability of ARFF vehicles, so that responses to emergency situations can be carried out quickly and effectively. Therefore, better personnel training and more detailed maintenance planning are needed to improve operational performance.